2008
DOI: 10.3354/ab00043
|View full text |Cite
|
Sign up to set email alerts
|

High reproduction, but low biomass: mortality estimates of the copepod Acartia tonsa in a hyper-eutrophic estuary

Abstract: Production, abundance and mortality of the copepod Acartia tonsa were studied for a period of 9 d in a hyper-eutrophic estuary, Mariager Fjord, Denmark. The estuary is characterised by oxygen-depleted and often sulphidic bottom water, and a relatively sparse mesozooplankton community with low species diversity. During the study, an intense phytoplankton bloom consisting mainly of the diatom Skeletonema costatum developed with chlorophyll a concentrations reaching 46 μg l , and egg hatching success was > 90%, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Some studies described the detrimental effects of sulfides on copepods. For example, Tiselius et al (2008) reported that rich sulfide levels in deep water decreased the survivorship of A. tonsa. Exposure to sulfide also affected the survival rates of male Cletocamptus confluens (Vopel et al, 1998) and the hatching success of A. tonsa (Nielsen et al, 2006).…”
Section: Poor Water Quality During the Decay Of P Donghaiensementioning
confidence: 97%
“…Some studies described the detrimental effects of sulfides on copepods. For example, Tiselius et al (2008) reported that rich sulfide levels in deep water decreased the survivorship of A. tonsa. Exposure to sulfide also affected the survival rates of male Cletocamptus confluens (Vopel et al, 1998) and the hatching success of A. tonsa (Nielsen et al, 2006).…”
Section: Poor Water Quality During the Decay Of P Donghaiensementioning
confidence: 97%
“…Because the deeper part of the inner fjord is anoxic, there is no infauna and therefore no bioturbation. The Mariager Fjord has a sparse mesozooplankton community and periodically intense blooms of S. marinoi (38).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a favorable feeding environment can enable an animal to acclimate to salinity outside its optimum range (Lee et al 2013). Therefore, the distribution of a cope pod species in salinity space likely arises through a combination of salinity tolerance with behaviorally mediated retention mechanisms (Hough & Naylor 1991, Simons et al 2006, Kimmerer et al 2014a) and spatially variable growth and mortality (Barlow 1955, Stalder & Marcus 1997, Tiselius et al 2008) that may offset effects of unfavorable salinity (Lee et al 2013, Hammock et al 2016 or restrict distributions to only part of the tolerated range (Rippingale & Hodgkin 1975).…”
Section: Abiotic Control: Salinity Effectsmentioning
confidence: 99%